Biochar facilitates methanogens evolution by enhancing extracellular electron transfer to boost anaerobic digestion of swine manure under ammonia stress - Gaojun Wang; Peng Fu; Bo Zhang; Ji Zhang; Qiuyi Huang; Gaofei Yao; Qian Li; Mawuli Dzakpasu; Jianfeng Zhang; Yu-You Li; Rong Chen (Bioresource Technology, 2023)

Transcriptome analysis revealed water balance controlled by ZxOSCA1.1 and lateral root development are crucial strategies for Zygophyllum xanthoxylon - Gaofei Fu; Yulu Ma; Lin Li; Yue Wang; Shengdan Wu; Haiyang Guo; Linjing Zhang (South African Journal of Botany, 2023)

RIN enhances plant disease resistance via root exudate-mediated assembly of disease-suppressive rhizosphere microbiota - Keming Yang; Ruixin Fu; Haichao Feng; Gaofei Jiang; Omri Finkel; Tianyu Sun; Mingchun Liu; Baowen Huang; Shan Li; Xiaofang Wang; Tianjie Yang; Yikui Wang; et al. (Molecular Plant, 2023)

The cell cycle arrested results in the premature advent of apical leaflets development cessation in Zygophyllum xanthoxylon - Gaofei Fu; Jing Li; Lin Li; Shengdan Wu; Yanbo Wu; Yue Wang; Cui Liu; Linjing Zhang (Trees, 2023)

Competition between biogeochemical drivers and land-cover changes determines urban greening or browning - Long Li; Wenfeng Zhan; Weimin Ju; Josep Peñuelas; Zaichun Zhu; Shushi Peng; Xiaolin Zhu; Zihan Liu; Yuyu Zhou; Jiufeng Li; Jiameng Lai; Fan Huang; et al. (Remote Sensing of Environment, 2023)

Biochar-assisted anaerobic membrane bioreactor towards high-efficient energy recovery from swine wastewater: Performances and the potential mechanisms - Gaojun Wang; Guohao Liu; Gaofei Yao; Peng Fu; Changxi Sun; Yu Li; Qian Li; Yu-You Li; Rong Chen (Bioresource Technology, 2023)

Radiation‐constrained boundaries cause nonuniform responses of the carbon uptake phenology to climatic warming in the Northern Hemisphere - Adrià Descals; Aleixandre Verger; Gaofei Yin; Iolanda Filella; Yongshuo H. Fu; Shilong Piao; Ivan A. Janssens; Josep Peñuelas (Global Change Biology, 2023)
Climatic warming has lengthened the photosynthetically active season in recent decades, thus affecting the functioning and biogeochemistry of ecosystems, the global carbon cycle and climate. Temperature response of carbon uptake phenology varies spatially and temporally, even within species, and daily total intensity of radiation may play a role. We empirically modelled the thresholds of temperature and radiation under which daily carbon uptake is constrained in the temperate and cold regions of the Northern Hemisphere, which include temperate forests, boreal forests, alpine and tundra biomes. The two‐dimensionality of the temperature‐radiation constraint was reduced to one single variable, θ , which represents the angle in a polar coordinate system for the temperature‐radiation observations during the start and end of the growing season. We found that radiation will constrain the trend towards longer growing seasons with future warming but differently during the start and end of season and depending on the biome type and region. We revealed that radiation is a major factor limiting photosynthetic activity that constrains the phenology response to temperature during the end‐of‐season. In contrast, the start of the carbon uptake is overall highly sensitive to temperature but not constrained by radiation at the hemispheric scale. This study thus revealed that while at the end‐of‐season the phenology response to warming is constrained at the hemispheric scale, at the start‐of‐season the advance of spring onset may continue, even if it is at a slower pace.